THE EFFECT OF GIVING BRAN AND COPRA MEAL FERMENTATION ON POPULATION GROWTH OF Daphnia magna - Fardha Ilman (Universitas Mataram, 2019)
The aim of this study was to determine the formulation of bran and copra meal which produced the highest growth of Daphnia magna. The research use Complete Random Design method that consist of 5 treatments and repeated 3 times. All containers are filled with 2 liters of water with a density of Daphnia magna which is 20 ind/l. Treatment A: giving 100% bran, treatment B: giving 75% bran and 25%, copra meal, treatment C: giving 50% bran and 50% copra meal, treatment D: giving 25% bran and 75% copra meal and treatment E: giving 100% copra meal. The results showed that all treatments have a significant effect on population growth, but do not have on biomass production and death phase. Giving 50% bran and 50% copra meal is the best formulation compared to other treatments with a total density of 173,33 ind/l.